Pengaruh Penerapan E-Kinerja Dan Budaya Kerja Terhadap Produktivitas Kerja Aparatur Sipil Negara Di LPP TVRI Stasiun Gorontalo - Indradjid Uno , Ali; Upe , Rachman; Firdaus, Adhy (Sekolah Tinggi Ilmu Ekonomi Ganesha, 2024)
E-Kinerja as a web-based innovation (E-Layanan) is very helpful for leaders in objectively assessing ASN or state civil apparatus’ performance, as well as to implement effective, efficient, transparent and accountable performance. This study aims to determine the effect of implementing E-Kinerja and work culture on the work productivity of ASN at the TVRI Gorontalo Station as a Public Broadcasting Institution (LPP). The research method utilized a design of quantitative approach, specifically deploying survey explanatory, which is a study that highlights the influence between the independent variables of the application of E-Kinerja (X1) and work culture (X2) with the dependent variable of work productivity (Y). The number of respondents included were all ASN either civil servants or government employees with employment agreement or PPPK, accumulating 43 people. The main data was collected via questionnaires, documentations, literature and observations. The data analysis technique used is multiple linear regression analysis. Based on the results of analysis, there is a positive and significant relationship, both partially between the E-Kinerja variable (X1) and Work Productivity (Y), Work Culture variable (X2) and Work Productivity (Y), or simultaneously between the E-Kinerja variable ( X1) and Work Culture (X2) with Work Productivity (Y). It is expected that the management of LPP TVRI Gorontalo Station will further intensify the application of E-Kinerja as a work culture that is able to increase organizational work productivity on an ongoing basis, focusing more on other variables that affect ASN work productivity that have not been detected in this study other than the application of E-Kinerja and work culture, and in human resource management (HRM) practices, it would also be able to shape capability and commitment in accordance to the characteristics of company or organization through both a soft and hard approach.